El Shatt: Memories of a Yugoslav Partisan refugee camp travelling from North Africa to Croatia - Hameršak, Marijana; Lingelbach, Jochen (Memory Studies, 2025)
From early 1944 until 1946, more than 25,000 refugees from Yugoslavia, mostly from the Dalmatian coast and islands, stayed in refugee camps in Egypt at El Shatt. Located on the shores of the Suez Canal, this complex of tented camps on desert sands was jointly run by the British military, Yugoslav Partisans and international humanitarian organizations. After the war, most of the refugees returned to their homes and only a five-pointed star-shaped cemetery overlooked by the statue of a grieving Mother remained on the spot. This article shows that unlike most refugee camps, El Shatt was not forgotten after its closure, but instead memorialized from the very beginning. Based on extensive research in United Nations, British and Croatian archives, we ask how the camps in El Shatt were memorialized in changing circumstances from their closure to today. How was their memory integrated into dominant historical narratives and practices, and what roles did local, intimate individual and family experiences and practices play in this? Reasons for not forgetting El Shatt start with the extraordinary documentation of these camps because they stood at the beginning of the UN-centred international humanitarian regime and the founding of Socialist Yugoslavia. For the continuous memorialization, however, it was important that the refugees returned as a large group to Dalmatia, the same region where they had come from. The local communities of memories provided the foundation for the abundant movement and communication of memories of El Shatt across different registers, spaces, genres, times and media.
Keywords: Camps; Croatia; Dalmatia; Egypt; memories; Refugees; Yugoslavia